Penerapan Pendekatan Pendidikan Matematika Realistik terhadap Kemampuan Pemahaman Konsep dan Penalaran Matematis Siswa - Merina Merina; Aritsya Imswatama; Hamidah Suryani Lukman (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
This article discusses the application of Realistic Mathematics Education approaches against the ability of mathematical reasoning and understanding of the students. The purpose of this research is to 1) know the comparison the ability between students who learn to use Realistic mathematics education approach with scientific approach, 2) know the comparative ability of reasoning mathematically between students who learn to use Realistic mathematics education approach with scientific approach, 3) know the difference between the understanding of mathematical concepts and reasoning of students. Data collection techniques was in the form of test result data post test as the learning outcomes of students. The data analysis used t test with two samples and test the correlation with significance level 0.05. As for the results of the analysis of the data shows that the 1) the ability of understanding the concept of students who use Realistic mathematics education approach better than students who use scientific approach, 2) mathematical reasoning ability of students using Realistic mathematics education approach better than students who use scientific approach, 3) there is a connection between the understanding of mathematical concepts and reasoning of students.